The fragility of borderlessness: Ricoeur's critical hermeneutics of cosmopolitan hospitality - Remodo, Adrian V. (Animo Repository, 2022)
Cosmopolitanism affirms universal human dignity and the rights that flow from it. Compared to the highly economic and political orientation of globalization, it centers on arriving at and cultivating ethical principles that ground the said assertion. While it does not deny that particular sovereign states and cultural identities still matter, it argues that dignity calls for mutual recognition beyond borders. This dissertation takes these cosmopolitan principles as springboards to argue for the centrality of the notion of hospitality in this particular geopolitical imagination. Using the phenomenological, hermeneutic, and political philosophies of Paul Ricoeur, this research maps interweaving arguments based on the following concepts: critical hermeneutics, fragility, and hospitality. Cosmopolitan imagination necessitates a prudential analysis of the power relations between the universal and the particular, the global and the local. In this context, this research uses the lens of critical hermeneutics to analyze these tensions. Moreover, this study proposes three forms of fragility arising from the dialectical relations involved in cosmopolitan imagination. Ontological fragility refers to the difficult path that an agent must take in order to maintain its selfhood; hermeneutic fragility shows how the finite human interpretation, where the possibility of errors is always incumbent, is challenged by the necessity of arriving at the most plausible political decision; and political fragility refers to the political situation where building a just and ethical society is constantly tested by the realist tendency towards economics and power. Finally, the notion of hospitality, under the models of translation, narrative exchange, and forgiveness, attempts to confront these kinds of fragility that cosmopolitanism proffers. The main question of this research is, “does Ricoeur’s understanding of hospitality offer a viable model for cosmopolitanism?” The discussions on the other two paradigms employed in this research, namely, the justice model and cultural model, affirms the significance of their specific fields of engagements. Nevertheless, this study affirms that the desire to welcome alterity is at the core of these two models. This priority of hospitality serves as the ground to argue that Ricoeur’s political philosophy is a feasible cosmopolitan philosophy. Keywords: Cosmopolitanism, Fragility, Hermeneutics, Hospitality, Planetary Consciousness, Ricoeur